Revision of the Genus Sirodotia Kylin (Batrachospermales, Rhodophyta) with Description of Four New Species - Rossignolo, Natalia L. [UNESP]; Vis, Morgan L.; Paiano, Monica O.; Eloranta, Pertti; West, John A.; Ganesan, E. K.; Yasmin, Farishta; Lim, Phaik-Eem; Necchi, Orlando [UNESP] (Museum National d'Histoire Naturelle, Paris, France, 2021)
Most genera of the freshwater red algal order Batrachospermales have been systematically revised using molecular and morphological data, but Sirodotia Kylin remains to be thoroughly reviewed. In this investigation, DNA sequence data for the rbcL, COI-5P and LSU markers of specimens collected worldwide were combined with morphological observations to assess their specifc diversity, infer their relationships and evaluate the morphological characters relevant for species identifcation. Phylogenetic analyses showed the genus to be a monophyletic lineage with high support. Inter-and intra-specifc divergence values were well-delineated with higher interspecifc (2.1-7% and 4.4-10.5%) and lower intraspecifc (0-2.4% and 0-3.8%) variations for rbcL and COI-5P sequences, respectively. LSU sequences revealed lower interspecifc divergence values than the COI-5P sequences (0.7-3.3%) indicating less resolution as a barcode marker. Nine species are recognized based on DNA sequence data, morphological characters and geographic distribution. Five species were previously described (S. assamica Necchi, Rossignolo, Yasmin, J.A.West & Ganesan, S. delicatula Skuja, S. huillensis (Welwitsch ex West & GSWest) Skuja, S. kennedyi A.L.Szinte, J.C.Taylor & M.L.Vis and S. suecica Kylin) and four new species are proposed (S. amazonica Necchi, N.L.Rossignolo & M.O.Paiano, sp. nov., S. aquiloamericana Necchi, N.L.Rossignolo & M.L.Vis, sp. nov., S. cryptica Necchi, N.L.Rossignolo & M.O.Paiano, sp. nov. and S. delicatuliformis Necchi, N.L.Rossignolo & M.O.Paiano, sp. nov.). Diagnostic characters for the genus are confrmed to be carpogonia asymmetric with a basal protuberance and carposporophytes di?use with indeterminant prostrate flaments producing determinate erect branches terminating in carposporangia. Te following morphological characters were applied to distinguish species: primary fascicle cell number, spermatangial arrangement, origin of gonimoblast flament and size of carposporangia. Based on morphology, S. sinica, S. segawae and S. yutakae are proposed as synonyms of S. suecica and S. ateleia Skuja of S. delicatula. Te status of three species (S. cirrhosa Skuja ex M.S.Balakr. & B.B.Chaugule, S. gardneri Skuja ex Flint and S. huangshanensis Z.X.Shi & S.L.Xie) could not be confrmed due to lack of type specimens and published information on informative diagnostic characters.
Keywords: Batrachospermales; biogeography; COI-5P; freshwater red algae; LSU; molecular systematics; rbcL; Sirodotia